Comparative Study of Soft In-Plane and Stiff In-Plane Tiltrotor Blade Aerodynamics in Conversion Flight, Using CFD-CSD Coupling Approach - Zhiyuan Hu; Peng Yu; Guohua Xu; Yongjie Shi; Feng Gu; Aijun Zou (Aerospace, 2024)
Tiltrotors permit aircrafts to operate vertically with lift, yet convert to ordinary forward flight with thrust. The challenge is to design a tiltrotor blade yielding maximum lift and thrust that converts smoothly without losing integrity or efficiency. The two types of blades, soft in-plane and stiff in-plane—the designation depending on the value of the blade’s natural lag frequency—exhibit different structural responses under the same flight conditions, differently affecting the aerodynamics of the blades, especially in the complex aerodynamic environment of conversion flight where the aerodynamic differences are significant. This phase of flight is not deeply researched, nor is the analytical coupling method much used. To study the influence of blade type on aerodynamics during conversion, models suitable for the conversion flight simulation are established for the application of coupled computational fluid dynamics and computational structural dynamics (CFD-CSD) methods. Each method is implemented with well-accepted techniques (the Unsteady Reynolds-Averaged Navier–Stokes (URANS) equations, the Reverse Overset Assembly Technique (ROAT), and the Timoshenko beam model. To improve the solving efficiency, a loose coupling strategy is used in constructing the two-way coupled model. The XV-15 tiltrotor is used for verification. The aeroelastic simulation of soft in-plane and stiff in-plane blades in conversion flight indicates an impactful role on the modal shapes, with a significant difference in the third flap modal shapes for the XV-15 rotor. However, the effect on aerodynamic performance is relatively small. In the first half of the flight conversion, the thrust of stiff in-plane blades is larger than that of soft in-plane blades, but in the last half, the influence of structural characteristics on aerodynamic performance is negligible and the thrust of the blades tends to be equal.